Intravascular leiomyomatosis in postmenopausal woman: a case report - Tingting Jiang; Yalan Yang; Li Wang (Frontiers in Medicine)
Intravenous leiomyomatosis (IVL) is a rare benign tumor originating from the smooth muscle of the uterus. Tumor cells spread along the veins, which may involve the uterine veins, pelvic veins, inferior vena cava, and even the right atrium. This case report describes a postmenopausal woman with IVL extending into the right heart chambers. The patient successfully underwent surgery and was discharged without complications. This report highlights valuable insights into the preoperative diagnosis and clinical management of IVL.